Study on the Performance of a Sirocco Fan (Optimum Design of Blade Shape) - Tsutomu Adachi; Naohiro Sugita; Yousuke Yamada (International Journal of Rotating Machinery)
A sirocco fan is a centrifugal fan with a forward curved blade. It is used for low pressure but has a large discharge use. In this paper, at first, nine impellers with various blade shapes were tested in the same casing. The measurements of the three-dimensional time variant velocity at the outlet of the impeller were done using four impellers having better performances among them. The relations between fan performance and outlet velocity were considered. The effects of the blade shape on the performance were considered. The blade inlet and outlet angles and blade inclination angles which have the best performance were considered. The design parameters of designing a sirocco fan impeller was described.